The Story of Rising Corruption Post-Village Government Reform - A View of Three Theories: Fraud, Managerial Hegemony, and Culture - Hafiez Sofyani; Rizal Yaya; Harjanti Widiastuti (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: This study investigates how corruption increased in the Indonesian village governments following village governance reform by ratifying the New Village Law of 2014. Also, the current research identifies gaps that trigger corruption.Design/Methodology/Approach: Three theories, i.e., fraud hexagon, managerial hegemony, and cultural dimensions, were employed as points of view. Due to investigation purposes, a qualitative approach is considered the most suitable method for this study. Hence, the interview was employed as data collection. The data were then analyzed using a deductive thematic analysis approach.Research findings: The results showcased that aside from personal interests, corruption occurred to crowd campaign financing for the head village election by the incumbent. The corruption types could be the embezzlement of village funds and village-owned enterprise funds and the establishment of ghost (fictitious) villages. The results also identified some factors triggering graft corruption scandals, namely poor governance practices, including accountability, transparency, and valid administration; the excessive authority of actors (village heads) in holding and managing village money; lack of participation mechanism.Practical and Theoretical contribution/Originality: To tackle corruption in the village government, strengthening proper good governance practices must be tightened, not merely as ritual or ceremonial. In addition, discussions of three theoretical perspectives, fraud, managerial hegemony, and culture, are presented in this paper.